The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1021/acssuschemeng.1c05230
|View full text |Cite
|
Sign up to set email alerts
|

Screening Ionic Liquids by the COSMO-RS Method for the Preparation of Antibacterial Cellulose Fibers

Abstract: The application of natural antibacterial agents seems to be one of the popular research topics in the field of antibacterial materials due to their unique properties such as good biocompatibility and biodegradability. In this work, 1-ethyl-3-methylimidazolium diethylphosphate ([Emim]DEP) with a better ability to dissolve three natural antibacterial agents (thymol, quercetin, and aloeemodin) was screened out from 195 kinds of ILs formed by 13 cations and 15 anions using the conductor-like screening model for re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…The absorption peaks at 2895, 1629, 1368, and 1072 cm –1 were assigned to the asymmetric stretching of −C–H, the −OH bending vibration of cellulose, the shear peak of −CH 2 , and the stretching vibration of C–O–C, respectively. The absorption peak at 906 cm –1 was caused by β-glycosidic bonds, which represented the amorphous area of cellulose . Except for the characteristic peaks of cellulose and quercetin, no peaks belonging to other structures were found.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The absorption peaks at 2895, 1629, 1368, and 1072 cm –1 were assigned to the asymmetric stretching of −C–H, the −OH bending vibration of cellulose, the shear peak of −CH 2 , and the stretching vibration of C–O–C, respectively. The absorption peak at 906 cm –1 was caused by β-glycosidic bonds, which represented the amorphous area of cellulose . Except for the characteristic peaks of cellulose and quercetin, no peaks belonging to other structures were found.…”
Section: Resultsmentioning
confidence: 99%
“…Our group has successfully screened and prepared antibacterial cellulose fibers by blending natural antibacterial agents into fibers and using ionic liquids (ILs) as the solvents. It was found that the loss rate of the antibacterial agent within the fiber prepared by the blending method was up to 50%, and the antibacterial activity decreased significantly from approximately 90% to about 60% after 30 washing cycles , because the antibacterial agents tend to enter the coagulation bath with the solvents or become suspended in the washing bath during the coagulation and washing processes. Coating antibacterial agents within microcapsules or chemical grafting it to RCF could reduce the loss of antibacterial agents, but these methods are complex and costly, making it a challenge to be implemented in industry.…”
Section: Introductionmentioning
confidence: 99%
“…[Emim]DEP was synthesized according to the previously reported 44 . The FT‐IR and 1 H NMR characterization results of [Emim]DEP were also displayed in the Supporting Information (Figure S7 and Figure S8).…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Increased foodborne microbial illness has raised global concerns because it causes millions of deaths every year and continues to severely jeopardize public health worldwide. Consequently, this has motivated massive scientific research and investment in the design and development of novel and versatile antimicrobial materials to overcome microbial invasions and for preventing pathogenic infections. Controlling bacterial infections is critical not only for preventing global outbreaks but also for applications ranging from health care to improving daily life quality. , Over the past few years, there has been a significant increase in consumer interest in high-quality and safe food products. , Different strategies have been applied to develop new polymeric materials by incorporating antimicrobial agents to minimize the proliferation of microbes observed on various food packages. , Blending of polymers with conventional antibacterial agents has gained wide attention and has been applied to inhibit microbial growth in food products. , Data from previous studies clearly show that polymers can be functionalized with N-halamine precursors and related compounds, which could be a useful tool for the decontamination of food pathogens such as Listeria, yeasts, molds, and mesophiles found on solid surfaces. However, the leaching of conventional agents and the release of free chlorine from the materials pose a serious threat to human health and the environment. , Lately, photodynamic inactivation, a relatively novel technology, has emerged as a potential option for preventing microbial inhibition and preserving food quality and shelf-life . Nowadays, photoactive compounds have garnered considerable interest in the development of food packaging films because of their capability to produce oxidative biocide-reactive oxygen species (ROS) in many polymeric materials, durability for repeated uses, and lower-toxicity suitable for food contacts .…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Blending of polymers with conventional antibacterial agents has gained wide attention and has been applied to inhibit microbial growth in food products. 13,14 Data from previous studies clearly show that polymers can be functionalized with N-halamine precursors and related compounds, which could be a useful tool for the decontamination of food pathogens such as Listeria, yeasts, molds, and mesophiles found on solid surfaces. 15−19 However, the leaching of conventional agents and the release of free chlorine from the materials pose a serious threat to human health and the environment.…”
Section: Introductionmentioning
confidence: 99%